RANCANG BANGUN APLIKASI KOMUNITAS MENDONGENG BERBASIS ANDROID - Kusuma Nata, Agus Wisnu; Arsa Suyadnya, I Made; Care Khrisne, Duman (Jurnal SPEKTRUM, 2022)
The culture of giving fairy tales to children has an important role in the development of their thinking patterns. This culture is starting to be abandoned and wants to be preserved again by the Bali Storytelling community. The community regularly holds or fills an event with storytelling activities. This study designs and builds an android-based mobile application for the storytelling community in managing community information such as managing information on storytelling activities, managing activity participants, managing fairy tale content, recruiting community members, and managing collaboration invitations aimed at the storytelling community. The application is built with the Flutter framework as the application frontend and the Laravel framework as a REST API which acts as an intermediary for data flow between application and database. The results of the black box test show that the application can run all functionality well and the results of the System Usability Scale test, the application gets a score of 73,375 which indicates the application is classified as good and can be accepted by the user.